The Effect Of Continuous Passive Motion After Repair Of Achilles Tendon Ruptures - Ertem, Kadir; Elmali, Nurzat; Inan, Muharrem; Harma, Ahmet; Ayan, Irfan; Karakaplan, Mustafa (Annals of Medical Research, 2021)
None